Instability of the interface of viscous fluids moving in a channel part I. A linear problem - Tran Van Tran; Nguyen Trung Ha (Vietnam Journal of Mechanics)
In this paper the linear problem of hydrodynamic stability of the interface between two viscous fluids, moving in a plane channel is considered. Thomas’s method of finite differences is used for solving this problem. The calculation indicates that the flow with an interface is more unstable than that of homogeneous fluid.